Teen pregnancy - Friedman, Lauri S. (Farmington Hills, MI : Greenhaven Press, 2010)
Discusses the social implications of teenage pregnancy, while teaching you the basics of writing an essay.
Teen pregnancy and adoption -- Opposing viewpoints on teen pregnancy -- Viewpoint one: teaching teens about birth control reduces teen pregnancy / Cecile Richards -- Viewpoint two: teaching students about abstinence reduces teen pregnancy / Katherine Bradley and Christine Kim -- Viewpoint three: giving teens emergency contraception can prevent teen pregnancy / Lisa Waller and William Bryson -- Viewpoint four: teens should not have access to emergency contraception / Teens for Life -- Viewpoint five: pregnant teens should need parental permission to get an abortion / National Right to Life Educational Trust Fund -- Viewpoint six: pregnant teens should not need parental permission to get an abortion / Bixby Center for Global Reproductive Health -- Model essays and writing exercises -- Preface A: the five-paragraph essay -- Preface B: the persuasive essay -- Essay one: poverty causes teen pregnancy -- Exercise 1A: create an outline from an existing essay -- Exercise 1B: create an outline for your own essay -- Essay two: Christian conservatives are to blame for the rise in teen pregnancy -- Exercise 2A: create an outline from an existing essay -- Exercise 2B: identify persuasive techniques -- Essay three: why parental involvement laws are always wrong -- Exercise 3A: examining introductions and conclusions -- Exercise 3B: using quotations to enliven your essay -- Final writing challenge: write your own persuasive five-paragraph essay -- Supporting research material.
Includes bibliographical references and index.
Keywords: Teenage pregnancy -- Juvenile literature; Sex instruction for teenagers -- Juvenile literature; Emergency contraceptives -- Juvenile literature